The Dispositions of A Caring English Teacher in Motivating Students in Learning English in SMKN 7 Samarinda - Talitha Rahmawati Lahay; Susilo; Sunardi (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2018)
Teacher has an important role in teaching-learning process. Teacher does not only teach the students, but also educates them. A caring teacher has a role to create a positive environment. When the teacher can create a positive environment, the students will feel comfortable and confident to learn the lesson well. This study involved an English teacher who had the criteria of a caring teacher as the subject. The purposes of this study are: (1) To find out the dispositions of a caring English teacher found in SMKN 7 Samarinda (2) To find out students’ perspectives toward their caring English teacher in motivating them in learning English. The design of this study was a descriptive qualitative research. The data were taken from observations and interviews with teacher and students. To identify the dispositions of a caring teacher, a theory by Carloz F. Diaz et al. (2005) was applied. In analyzing the data, the researcher used Miles and Huberman’s Framework (1994). The result of this study showed that (1) There were three dispositions found in the English teacher, they were: respect all students, believe that all children could learn, and classroom for social justice. It meant that the teacher was a caring teacher. By being a caring teacher, the students were more motivated to learn English. (2) Based on students’ perspective, it was shown that the teacher was a caring teacher, and their caring teacher motivated them to learn English better. Students appreciated that their teacher respected them, he often motivated them to learn English, and he was fair and equal to them all